2003
DOI: 10.1080/01411920301841
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of National Value‐added Datasets to Assess the Impact of Selection on Pupil Performance

Abstract: The impact of selective education systems on pupil performance has long been a contentious issue, but the advent of national value-added datasets linking performance across key stages for the majority of pupils in England has enabled detailed analysis to throw some light on the issues. The main finding has been a distinct difference in Key Stage 3 test levels for pupils on the 'borderline' between grammar school and secondary modern school, even when prior attainment is taken into account. Possible explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 1 publication
0
17
0
1
Order By: Relevance
“…The OECD has conducted a series of comparative studies of national educational performance and these have concluded that more differentiated systems, where children are selected onto different tracks at an early stage, are less effective in achieving higher overall attainment than less differentiated systems (OECD/UNESCO‐UIS, 2003). With regard to the relative effectiveness of schools Schagen and Schagen (2002, 2003a, b) and Atkinson and Gregg (2004) found that while standards at school level showed that children at grammar schools performed better than children at secondary modern schools, the standard at LEA level showed little difference compared with non‐selective LEAs. Pupil level data also reveal that grammar schools are still strongly associated with the social segregation of intakes.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…The OECD has conducted a series of comparative studies of national educational performance and these have concluded that more differentiated systems, where children are selected onto different tracks at an early stage, are less effective in achieving higher overall attainment than less differentiated systems (OECD/UNESCO‐UIS, 2003). With regard to the relative effectiveness of schools Schagen and Schagen (2002, 2003a, b) and Atkinson and Gregg (2004) found that while standards at school level showed that children at grammar schools performed better than children at secondary modern schools, the standard at LEA level showed little difference compared with non‐selective LEAs. Pupil level data also reveal that grammar schools are still strongly associated with the social segregation of intakes.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…This has been justified by the increasing amount of evidence to suggest that variables describing the financial circumstances of pupils are reliable in predicting many outcome measures relevant to educational research (for example, Schagen and Schagen 2003;Ruddock et al 2004;Strand and Demie 2005). In the UK the most accessible indicator of an individual pupil's socio-economic background is whether they are eligible for free school meals (FSM).…”
Section: Introductionmentioning
confidence: 98%
“…Models of attainment data (for example, Schagen and Schagen 2003) almost invariably contain eligibility for FSM as a significantly influential background variable. Eligibility for FSM is used in the calculation of the contextualised value-added measure by the UK Department for Children, Schools and Families (http://www.standards.dcsf.gov.uk/performance).…”
Section: Introductionmentioning
confidence: 99%
“… The present article does not discuss whether selection is a good thing—this important question is separate from the question of quality of selection in the selective system. For relevant research, see for example Schagen and Schagen (). …”
mentioning
confidence: 99%
“…The present article does not discuss whether selection is a good thing-this important question is separate from the question of quality of selection in the selective system. For relevant research, see for exampleSchagen and Schagen (2003). 2 Exact years are not given to protect the privacy of the school and pupils.3 In the psychometric literature, this scale is called 'Deviation IQ'.…”
mentioning
confidence: 99%